The Role of Halal Center in Increasing Sustainable Economy in the Halal Industry Sector - Rahmat Husein Lubis; Fatwa Syibromalisi (Journal of Islamic Economics and Finance Studies, 2023)
The role of the Indonesian Ulama Council (MUI) in halal labeling is still considered ineffective. So, the government enacted Law Number 3 of 2014 concerning Halal Product Guarantees. Through this regulation, the authority for halal certification is given to BPJPH, through the Halal Center. The role of the Halal Center in improving the halal economy also has various challenges in terms of human resources, producer compliance, and the need for cooperation with related institutions. This research aims to determine the role of halal centers in boosting the halal economy in the Indonesian halal industrial sector. This research is a qualitative descriptive type of research. The research sources used come from books, scientific journals, encyclopedias, literature, works of scientists, and relevant websites. The object of this research is the role of halal centers in improving a sustainable halal economy in the halal industrial sector. The results of this research can conclude that the role of halal centers through certification, education, product innovation, and supervision is considered effective in improving the halal economy in the halal industrial sector in Indonesia. It is proven that in 2020, the number of halal certification registrations was 11,103, and in 2023 the number increased to 155,451.   Peran Majelis Ulama Indonesia (MUI) dalam pelabelan halal masih dinilai belum efektif. Sehingga pemerintah menetapkan UU Nomor 3 Tahun 2014 tentang Jaminan Produk Halal. Melalui aturan tersebut, wewenang sertifikasi halal diberikan kepada BPJPH,  melalui Halal Center. Peran Halal Center dalam meningkatkan ekonomi halal juga memiliki berbagai tantangan baik dari sisi sumber daya manusia, kepatuhan produsen, serta perlunya kerja sama dengan intitusi yang berkaitan. Tujuan dari penelitian ini adalah untuk mengetahui peran dari halal center dalam mendongkrak ekonomi halal pada sektor industri halal Indonesia. Penelitian ini berjenis deskriptif kualitatif. Sumber-sumber penelitian yang digunakan berasal dari buku, karya ilmiah jurnal, ensiklopedia, literatur, karya ilmuan, serta website yang relevan. Objek pada penelitian ini yaitu mengenai peran halal center dalam meningkatkan ekonomi halal yang berkelanjutan di sektor industri halal. Hasil penelitian ini dapat disimpulkan bahwa peran dari halal center melalui sertifikasi, pendidikan, inovasi produk, dan pengawasan dinilai efektif dalam meningkatan ekonomi halal dalam sektor industri halal di Indonesia. Terbukti pada tahun 2020, jumlah pendaftaran sertifikasi halal sebanyak 11,103 dan pada tahun 2023 jumlahnya meningkat menjadi 155.451.